Genetics of hypertension-attributed chronic kidney disease in black South Africans - Nqebelele, Nolubabalo Unati (My University, 2018)
Background: Chronic kidney disease (CKD) is recognised as a global public health problem. Variants in apolipoprotein L1 (APOL1) gene were shown to associate with higher rates of nondiabetic kidney disease in African American patients compared with white patients. Frequencies of these variants differ substantially in African populations, with the highest frequency reported in west African populations, with complete absence in east African populations, suggesting that the contribution of these variants to kidney disease might also differ. As not all individuals at high genetic risk (presence of two APOL1 risk variants) develop kidney disease, it is possible that there are modifying factors which act as ‘second hits’ (other genes or environmental factors) interacting with APOL1 to initiate kidney disease. Aims: The aim of this thesis was to determine the association of the APOL1 variants with hypertension-attributed CKD in black South Africans. A further aim was to determine the associations of potential ‘second hits’, such as polyomavirus infections and polymorphisms in other genes, with hypertension-attributed CKD. Furthermore, we aimed to test the interactions of these ‘second hits’ with APOL1 risk variants. Methods: This was a cross-sectional study conducted in the Divisions of Nephrology at Charlotte Maxeke Johannesburg Academic Hospital and Chris Hani Baragwanath Academic Hospital, following approval from the Human Research Ethics Committee of the University of the Witwatersrand (Clearance certificate no M141192). Black patients with hypertension-attributed CKD, together with their first-degree relatives and healthy controls were included in the study after providing written informed consent. Blood samples were genotyped for polymorphisms in the APOL1, uromodulin, podocin, bone morphogenic protein 4 (BMP4) and serologically defined colon cancer antigen 8 genes, together with measurement of urinary uromodulin levels and quantification of polyomaviruses in urine. Results: Carriage of two APOL1 risk alleles (vs. zero or one risk allele) was not associated with hypertension-attributed CKD (OR 0.849; 95% CI [0.255 - 2.831]; p = 0.790). Absence of JCV DNA was strongly associated with hypertension-attributed kidney disease (OR 15.27; 95% CI [3.52 to 66.31]; p <0.001), with even higher odds ratio of 43-fold after correcting for age, sex, socioeconomic status and the number of APOL1 risk alleles. There was no significant interaction observed between the absence of JC virus and the presence of one or two APOL1 risk alleles. There was a trend for an increased risk of kidney disease in those who had two APOL1 risk variants and were major allele homozygotes at rs16854341 (podocin gene) (4.78 (95% CI [0.87 - 26.31]; p = 0.072) and at rs8014363 (BMP4 gene) (5.16 (95% CI [0.92 - 29.87]; p = 0.062. For each 1-standard deviation increase in urinary uromodulin level, the multivariable-adjusted odds ratio for CKD was 0.6 (95% CI [0.48 to 0.81]; p <0.01). Conclusion: Our study provides evidence that APOL1 risk variants are present in black South Africans, though their frequency does not differ between patients with hypertension-attributed CKD, their first degree relatives and healthy black South Africans. We showed a very strong association between the absence of JC viruria and hypertension-attributed CKD. In the presence of two APOL1 risk variants, major allele homozygotes in the podocin and BMP4 genes had a trend towards an increased risk of kidney disease. Further research with larger sample size and CKD of various etiologies and different stages of CKD are warranted.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg 2018
Keywords: Chronic rehal failure; Kidneys--Disease; Kidney Diseases